Do olive polyphenols negatively affect nutrient digestibility in pigs? - Jakob Leskovec; Alenka Levart; Janez Salobir; Vida Rezar (Journal of Central European Agriculture, 2018)
It is widely accepted that olive (Olea europaea L.) polyphenols (OP) have many favourable properties (e.g. antioxidative, antimicrobial, antifungal). OP can improve the growth and nutrient digestibility of animals via affecting digestion and health, even though they could negatively affect the mineral absorption by forming insoluble complexes with minerals in the intestine. In the present study, the effects of a dietary olive leaves extract (OLE) on nutrient digestibility in pigs were studied. Twenty-four weaned castrated male piglets were fed a no supplemented (C) or a supplemented diet with three different levels of OLE (O1, O2 and O3: 3.84 mg, 38.4 mg, 96 mg hydroxytyrosol equivalents/day, respectively). Retention and apparent total tract digestibility (ATTD) of dry matter (DM), crude protein (CP), crude fat (CF), organic matter (OM), nitrogen free extract (NFE), ash, neutral (NDF) and acid detergent fibres (ADF), gross energy (GE), Ca, P, Mg, Fe, Cu, Zn, K and Na were measured. Results showed that OLE lowered the retention of Fe and K, and revealed a numerical tendency to lower the retention of Cu and ATTD of Fe and Cu. In conclusion, a low dietary supplementation of OLE has no effect on the digestibility and retention of major nutrients, although some minor negative effects on mineral digestibility can be present.